Threats to Patient Safety in the Inpatient Maternity Setting. Issue 2 (March 2020) - O'Neill, Loraine; Miller, Lisa A.; Rohan, Annie J.
Abstract : Abstract: As part of our special topics issue on inpatient maternity care, experts were asked to offer their thoughts about the main issues putting mothers and babies at risk in the maternity inpatient setting and what quality and safety practices may be beneficial in keeping them safe from harm. Each of the experts has a unique perspective. Loraine O'Neill was one of the original perinatal patient safety nurses who were established as part of an effort by a professional liability company to promote patient safety in birthing hospitals that they covered in several states (Will, Hennicke, Jacobs, O'Neill, & Raab, 2006 ). She now is the perinatal patient safety officer in a large academic medical center in New York City. Lisa Miller is a well-known expert on fetal assessment during labor, certified nurse midwife, attorney, educator, patient safety expert, and editor of a popular fetal monitoring textbook (Miller, Miller, & Cypher, 2020 ). She has taught fetal monitoring to nurses, midwives, and physicians in multidisciplinary groups all over the United States and consulted on numerous patient safety initiatives. Annie Rohan is a dual-certified neonatal and pediatric nurse practitioner with a 30-plus year clinical practice career with infants, children, and families facing critical and chronic illness. She is currently a healthcare researcher, and oversees advanced practice and doctoral nursing programs at SUNY Downstate Health Sciences University. Abstract : As part of our special topics issue on inpatient maternity care, three nurse experts were asked to offer their thoughts about the main issues putting mothers and babies at risk in the hospital setting and what quality and safety practices may be beneficial in keeping them safe from harm.